Carcinoid tumor of the lung - Caruso, Enrique S. (Cirugía del Uruguay, 1997)
Laennec in 1831 was the first to recognize a benign-looking bronchial tumor; but it was Müller who in 1882 made the first pathological description and called it "bronchial adenoma".